Introduction: Italy in the EU—pigmy or giant?. Issue 2 (12th January 2016) - Fabbrini, Sergio; Piattoni, Simona
Summary: This introductory article discusses the circumstances under which Italy manages to forge 'national preferences' and push them through the European policy-making process. Drawing from the analysis of several policy areas, it concludes that Italy plays a major policy-making role, particularly when it acts as mediator between large countries and small- and medium-sized ones, and when it argues its case according to policy- and EU-appropriate logics. While Italy may not have it 'its way' all the time (as no member-state does), it still manages to influence the EU policy-making process more frequently and more significantly than the literature has so far conceded.